2017
DOI: 10.1002/cbin.10820
|View full text |Cite
|
Sign up to set email alerts
|

The post‐therapeutic effect of rapamycin in mild traumatic brain‐injured rats ensuing in the upregulation of autophagy and mitophagy

Abstract: Mild traumatic brain injury (mTBI), common in juveniles, has been reported to be caused by sports-related concussion. Many young children may suffer from post-concussion syndrome. mTBI, in early stages of life, could play a part in neuron apoptosis and degeneration, cognitive and motor coordination impairment, as well as dementia. Our study was aimed at further investigating the post-therapeutic efficacy of rapamycin in the recuperation of mTBI while at the same time investigating the metamorphosis in both aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Likewise, in individuals with CTE symptoms, similar phenotypic manifestations have been reported as the condition progresses (Omalu et al, ). Results from the studies assessed here indicate increased anxiety and impaired attention (Hehar, Yeates, Kolb, Esser, & Mychasiuk, ; Wang et al, ; Yamakawa, Salberg, et al, ). There was also a consistent depression‐like response to the forced swim task in mTBI groups, as evidenced by immobility and disinclination to swim (Salberg et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Likewise, in individuals with CTE symptoms, similar phenotypic manifestations have been reported as the condition progresses (Omalu et al, ). Results from the studies assessed here indicate increased anxiety and impaired attention (Hehar, Yeates, Kolb, Esser, & Mychasiuk, ; Wang et al, ; Yamakawa, Salberg, et al, ). There was also a consistent depression‐like response to the forced swim task in mTBI groups, as evidenced by immobility and disinclination to swim (Salberg et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Within this context autophagy of mitochondria might play an important positive homeostatic role of in endogenous metabolic rebalancing in acute injury, especially in TBI (Smith et al, 2011). In line with this, the induction of autophagy using rapamycin inhibited an important mitochondrial cell death pathway with decreased cyt c release and caspase 3 activation (Tang et al, 2016;Wang et al, 2017;Wu et al, 2017), while inhibition of mitophagy by mdivi-1-induced cyt c release and caspase 3 activa- Figure 8. PLS3 knockdown exacerbates neuronal injury and behavioral deficits after TBI.…”
Section: Discussionmentioning
confidence: 81%
“…V, Vehicle. et al, 2016;Liu et al, 2017b;Wang et al, 2017;Wu et al, 2017). A number of studies have reported presence of abnormal mitochondria early after acute injury, possibly associated with energy depletion and/or disturbed Ca 2ϩ homeostasis (Cheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, rapamycin has demonstrated beneficial effects in the context of acute CNS damage showing increased neuronal survival after spinal cord or brain injury as well as RGC rescue after optic nerve transection and ischaemia/reperfusion 36,56 . Rapamycin is well known to increase autophagy, and also upregulates mitophagy and mitochondrial fission in in vivo CNS damage models [73][74][75][76] . Supporting possible increase of mitophagy after ONC, EM pictures of RGCs after optic nerve transection show increased numbers of mitochondria in autolysosomes 6 days after the insult 36 .…”
Section: Discussionmentioning
confidence: 99%